The Influence of the Interactive Digital Media-Based Peer Lesson Method in Improving Values in SKI Learning - Tesya dela puspita; Muhammad Syaifullah; Luthfi Fadillah (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to determine and analyze the effect of the interactive digital media-based peer lesson method on improving grades in the Islamic Cultural History (SKI) subject at MA Darul Ulum. This study uses a quantitative approach with a Pre-Experimental One-Group Pretest-Posttest Design. The study population was 36 grade X students who were also sampled through a saturated sampling technique. The research instrument was 20 multiple-choice questions whose validity and reliability had been tested using product moment correlation and Cronbach's Alpha with the help of SPSS version 27. Data analysis was carried out through the Liliefors normality test, paired sample t-test for hypothesis testing, and the N-gain test to measure the effectiveness of the treatment. The results showed an increase in learning completeness from 53% in the pretest to 69% in the posttest. The calculated t value (3.461) was greater than the t table (2.021), so H₀ was rejected and H₁ was accepted. The N-gain value of 0.6445 was included in the moderate effectiveness category. Thus, the peer lesson method based on interactive digital media has a significant and quite effective influence in improving students' SKI learning outcomes.